Piezoelectric polymer film and preparation method and application thereof

By stretching, annealing and electric field polarization treatment of vinylidene fluoride-trifluoroethylene copolymer, piezoelectric polymer films with high voltage electrical properties are prepared, which solves the problem of low piezoelectric coefficient of existing materials and is suitable for a variety of application fields.

CN119708594APending Publication Date: 2025-03-28SHENZHEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411679181.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing polymer piezoelectric materials have low piezoelectric coefficients and are difficult to meet actual usage needs, especially in the fields of flexible wearable devices and biosensors.

Method used

By providing a method for preparing a piezoelectric polymer film, it includes stretching and annealing treatment using vinylidene fluoride-trifluoroethylene copolymer as a starting material, and applying an electric field to polarize after annealing to form a high content of β-crystalline crystalline and oriented amorphous structure.

Benefits of technology

Improves the piezoelectric properties of piezoelectric polymer films, enhances their flexibility and biocompatibility, making them suitable for wearable devices, sensors, actuators, medical monitoring and energy harvesting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708594A_ABST
    Figure CN119708594A_ABST
Patent Text Reader

Abstract

The invention discloses a piezoelectric polymer film and a preparation method and application thereof, and the preparation method of the piezoelectric polymer film comprises the following steps: providing a polymer film which comprises a vinylidene fluoride-trifluoroethylene copolymer; stretching the polymer film to enable the strain of the polymer film to reach 350%-650%; the stretched polymer film is annealed, the annealing temperature ranges from 70 DEG C to 150 DEG C, and the piezoelectric polymer film is obtained. The piezoelectric polymer film has a beta crystal form close to 100% and a large number of oriented amorphous structures, and is beneficial to enabling the vinylidene fluoride-trifluoroethylene copolymer to generate excellent piezoelectric performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer piezoelectricity, and in particular to a piezoelectric polymer film and a preparation method and application thereof. Background Art

[0002] Piezoelectric materials can realize the mutual conversion of mechanical energy and electrical energy, and are usually divided into two categories: inorganic and polymer piezoelectric materials. Traditional inorganic piezoelectric ceramics, such as lead zirconate titanate (PZT), have high piezoelectric coefficients and are widely used in energy harvesting and electromechanical sensing. However, they have high hardness, high specific gravity, and poor ductility, making them difficult to use in emerging fields such as flexible wearable devices and biosensors. Polymer piezoelectric materials, such as the common polyvinylidene fluoride (PVDF) and its polymers, have good flexibility and biocompatibility, and show great application potential in wearable devices, sensors, actuators, medical monitoring, and energy harvesting. However, their piezoelectric coefficients are low and it is difficult to meet actual usage needs. Summary of the invention

[0003] In view of this, the present application provides a piezoelectric polymer film and a preparation method thereof, as well as an application of the piezoelectric polymer film to solve at least one of the above problems.

[0004] To achieve the above-mentioned purpose, in a first aspect, the present application provides a method for preparing a piezoelectric polymer film, comprising: providing a polymer film, wherein the polymer film comprises a vinylidene fluoride-trifluoroethylene copolymer; stretching the polymer film so that the strain of the polymer film reaches 350% to 650%; and annealing the stretched polymer film, wherein the annealing temperature is 70°C to 150°C, to obtain the piezoelectric polymer film.

[0005] In some possible implementations, the annealing temperature is 120° C. to 140° C., and the annealing time is 20 h to 26 h.

[0006] In some possible implementations, the preparation method further includes applying an electric field to the annealed polymer film for polarization, and the intensity of the electric field is 100 MV / m to 200 MV / m.

[0007] In some possible implementations, in the vinylidene fluoride-trifluoroethylene copolymer, the molar content of trifluoroethylene is 40% to 60%.

[0008] In some possible implementations, the weight average relative molecular mass of the vinylidene fluoride-trifluoroethylene copolymer is 400,000 g / mol to 550,000 g / mol.

[0009] In some possible implementations, providing the polymer film includes mixing vinylidene fluoride-trifluoroethylene copolymer with a solvent, wherein the solvent includes one or more of N,N-dimethylformamide, acetone and dimethyl sulfoxide to obtain a mixed solution, and drying the mixed solution to obtain the polymer film.

[0010] In some possible implementations, in the mixed solution, the concentration of the vinylidene fluoride-trifluoroethylene copolymer is 61 mg / mL to 83 mg / mL.

[0011] In some possible implementations, the drying temperature is 35° C. to 65° C., and the drying time is 20 h to 26 h.

[0012] In some possible implementations, the polarization includes unidirectional polarization, and the number of unidirectional polarizations is 20 to 60 times.

[0013] The preparation method provided in the first aspect above uses vinylidene fluoride-trifluoroethylene copolymer as a polymer raw material to prepare a polymer piezoelectric film. Polyvinylidene fluoride can be crystallized into five crystal phases of α, β, γ, δ and ε under different conditions. α and ε are non-polar phases, while β, γ and δ are ferroelectric polar phases. These crystal forms correspond to three different conformations, namely, cis-trans alternating (TGTG') conformation, all-trans conformation (TTTT) and intermediate conformation (T3GT3G'). Among them, the polar β crystal form in which the molecule is in an all-trans conformation is the most ideal piezoelectric crystal phase, because almost all fluorine atoms and hydrogen atoms are located on opposite sides of the chain, which helps to produce high polarity. The trifluoroethylene copolymer unit introduced by the vinylidene fluoride-trifluoroethylene copolymer can provide a certain steric hindrance, forcing vinylidene fluoride to adjust to an all-trans conformation, so as to more easily form a β crystal phase in the copolymer. The above preparation method is not only conducive to the formation of oriented crystals by applying stress to the polymer film for stretching and annealing, but also can induce a large number of oriented amorphous structures to form at the interface between the crystalline region and the amorphous region. At the same time, the oriented amorphous structure is more sensitive to the annealing temperature. In the present application, by stretching the polymer film to a preset stretching ratio and then annealing, when the annealing temperature is controlled within a preset range, it is conducive to forming more oriented amorphous structures, so that the obtained piezoelectric polymer film can have higher piezoelectric properties. The above preparation method can further apply a certain electric field to the stretched and annealed polymer film for polarization, which is conducive to further orienting the molecular dipoles, thereby improving the piezoelectric performance.

[0014] When the molar content of trifluoroethylene in the vinylidene fluoride-trifluoroethylene copolymer is more than 18%, the polyvinylidene fluoride-trifluoroethylene almost always presents an all-trans conformation, and its corresponding crystal form is β crystal. Therefore, in some possible implementations of the preparation method provided in the first aspect above, when the molar content of trifluoroethylene in the selected vinylidene fluoride-trifluoroethylene copolymer is 40% to 60%, the copolymer always presents an all-trans conformation, showing a β crystal form close to 100%, which is conducive to obtaining higher polarity.

[0015] In a second aspect, the present application provides a piezoelectric polymer film prepared by the above-mentioned preparation method.

[0016] The piezoelectric polymer film of the present application has a β-crystal structure close to 100% and good orientation. By regulating it to have a higher content of oriented amorphous structure, it is beneficial to improve the piezoelectric properties of the vinylidene fluoride-trifluoroethylene copolymer.

[0017] In a third aspect, the present application provides a piezoelectric body comprising the above-mentioned piezoelectric polymer film.

[0018] The piezoelectric polymer film of the present application has good flexibility and biocompatibility, as well as excellent piezoelectric properties. It is used in piezoelectric bodies, such as wearable devices, sensors, actuators, medical monitoring and energy harvesting devices, which is beneficial to improving the conversion efficiency between mechanical energy and electrical energy of the piezoelectric body. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The direct piezoelectric coefficient test results of the piezoelectric polymer film provided in the embodiments of the present application. DETAILED DESCRIPTION

[0020] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0021] In order to improve the piezoelectric properties of polymers, researchers usually add nanofillers to polymers to improve the piezoelectric properties. However, the addition of fillers is also limited. Adding too much filler can easily cause agglomeration. Another way is to regulate the polymer structure. This application improves the preparation method of piezoelectric polymer films, thereby regulating the polymer structure, studying the relationship between polymer structure and piezoelectric properties, and achieving the purpose of improving the piezoelectric coefficient of piezoelectric polymer films.

[0022] Based on this, an embodiment of the present application provides a method for preparing a piezoelectric polymer film, comprising: S100, providing a first polymer film, wherein the first polymer film includes a vinylidene fluoride-trifluoroethylene copolymer.

[0023] The present application uses vinylidene fluoride-trifluoroethylene copolymer as the polymer raw material to prepare a polymer piezoelectric film. Polyvinylidene fluoride can crystallize into five crystal phases, α, β, γ, δ and ε, under different conditions. α and ε are non-polar phases, while β, γ and δ are ferroelectric polar phases. These crystal forms correspond to three different conformations, namely the cis-trans alternating (TGTG') conformation, the all-trans conformation (TTTT) and the intermediate conformation (T3GT3G'). Among them, the polar β crystal form in which the molecule is in an all-trans conformation is the most ideal piezoelectric crystal phase, because almost all fluorine atoms and hydrogen atoms are located on opposite sides of the chain, which helps to produce high polarity. The trifluoroethylene copolymer unit introduced by the vinylidene fluoride-trifluoroethylene copolymer can provide a certain steric hindrance, forcing the vinylidene fluoride to adjust to the all-trans conformation, so as to more easily form a β crystal phase in the copolymer.

[0024] In some embodiments, in the vinylidene fluoride-trifluoroethylene copolymer, the molar content of trifluoroethylene is 40% to 60%. For example, the molar content of trifluoroethylene can be 40%, 42%, 45%, 48%, 50%, 52%, 55%, 57%, 60% or any value within the range composed of any two of the above values. In some embodiments, the weight-average relative molecular mass of the vinylidene fluoride-trifluoroethylene copolymer is about 400,000 g / mol to 550,000 g / mol. When the molar content of trifluoroethylene in the vinylidene fluoride-trifluoroethylene copolymer is more than 18%, polyvinylidene fluoride-trifluoroethylene almost always presents an all-trans conformation, and its corresponding crystal form is β crystal. Therefore, when the molar content of trifluoroethylene in the vinylidene fluoride-trifluoroethylene copolymer is controlled within the above range, the copolymer always presents an all-trans conformation, which is conducive to obtaining a higher polarity.

[0025] In some embodiments, the S100 may be implemented by the following S101: S101, mixing a vinylidene fluoride-trifluoroethylene copolymer with a solvent, wherein the solvent includes one or more of N,N-dimethylformamide, acetone and dimethyl sulfoxide, to obtain a mixed solution, and drying the mixed solution to obtain the polymer film.

[0026] Under the action of the above solvent, a vinylidene fluoride-trifluoroethylene copolymer solution with certain crystallinity, crystal phase and crystal size is formed. After drying, the solvent is appropriately volatilized to form a polymer film suitable for stretching.

[0027] In some embodiments, the concentration of the vinylidene fluoride-trifluoroethylene copolymer is 61 mg / mL to 83 mg / mL. For example, the concentration of the vinylidene fluoride-trifluoroethylene copolymer can be 61 mg / mL, 65 mg / mL, 70 mg / mL, 73 mg / mL, 75 mg / mL, 77 mg / mL, 80 mg / mL, 83 mg / mL or any value within the range formed by any two of the above values. Reasonable control of the amount of solvent and vinylidene fluoride-trifluoroethylene copolymer so that the concentration of the vinylidene fluoride-trifluoroethylene copolymer is controlled within the above range is conducive to improving the quality of the resulting polymer film to adapt to the tensile strain of the larger tensile ratio and maintain the material properties of the polymer film itself.

[0028] In some embodiments, the drying temperature is 35°C to 65°C, and the drying time is 20 h to 26 h. For example, the drying temperature can be 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, or any value within the range formed by any two of the above values. The drying time can be 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, or any value within the range formed by any two of the above values. Drying at a suitable temperature and time is conducive to controlling the rate of formation of the polymer film, fully volatilizing the solvent while maintaining the initial structural state of the copolymer in the solvent, and is conducive to achieving a controllable stretch ratio during the stretching process.

[0029] S200: stretching the polymer film so that the strain of the polymer film reaches 350% to 650%; and annealing the stretched polymer film at a temperature of 70°C to 150°C to obtain the piezoelectric polymer film. For example, the strain can reach 350%, 380%, 400%, 430%, 450%, 480%, 500%, 520%, 550%, 570%, 600%, 620%, 650% or any value within the range formed by any two of the above values. The annealing temperature can be 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or any value within the range formed by any two of the above values.

[0030] The present application applies stress to the polymer film for stretching and annealing, which is conducive to inducing the generation of a large number of oriented amorphous structures at the interface between the crystalline region and the amorphous region. At the same time, the oriented amorphous structure is sensitive to the annealing temperature. In the present application, by stretching the polymer film to a preset stretching ratio and then annealing, when the annealing temperature is controlled within a preset range, it is conducive to the formation of more oriented amorphous structures, so that the obtained piezoelectric polymer film can have higher piezoelectric performance.

[0031] It can be understood that the annealing heat treatment of the stretched polymer film in the present application can maintain a good polymer structural orientation, promote the formation of an oriented amorphous structure, and thus improve the piezoelectric performance.

[0032] In some embodiments, the annealing temperature is 120°C to 140°C, and the time is 20 h to 26 h. For example, the annealing temperature can be 120°C, 122°C, 124°C, 126°C, 128°C, 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, or any value within the range formed by any two of the above values. The annealing time can be 20h, 21h, 22h, 23h, 24h, 25h, 26h, or any value within the range formed by any two of the above values. When the annealing temperature is further controlled within the above range, the formation of an oriented amorphous structure in the polymer film can be better promoted, thereby further improving the piezoelectric constant of the resulting piezoelectric polymer film. It can be understood that controlling the annealing time within the above range is conducive to giving full play to the effect of annealing within a specific temperature range.

[0033] In some embodiments, after stretching and annealing the polymer film, the method further comprises the following step S210: S210, applying an electric field to the annealed polymer film for polarization, wherein the intensity of the electric field is 100 MV / m to 200 MV / m. For example, the intensity of the electric field can be 100 MV / m, 110 MV / m, 120 MV / m, 130 MV / m, 140 MV / m, 150 MV / m, 160 MV / m, 170 MV / m, 180 MV / m, 190 MV / m, 200 MV / m, or any value within the range formed by any two of the above values.

[0034] Further applying an electric field to the stretched and annealed polymer film for polarization is conducive to further inducing the formation of an oriented amorphous structure in the polymer film. An electric field with an intensity within a preset range is conducive to further inducing the formation of an oriented amorphous structure, thereby improving the piezoelectric performance.

[0035] In some embodiments, the polarization includes unidirectional polarization, and the number of unidirectional polarization is 20 to 60 times. For example, the number of unidirectional polarization can be 20 times, 25 times, 30 times, 35 times, 40 times, 45 times, 50 times, 55 times, 60 times, or any value within the range formed by any two of the above values. The above unidirectional polarization of the polymer film can increase the piezoelectric constant of the obtained piezoelectric polymer film.

[0036] An embodiment of the present application further provides a piezoelectric polymer film prepared by the above preparation method.

[0037] The piezoelectric polymer film of the present application has a β-crystal structure close to 100% and good orientation. By adjusting the film to have a higher content of oriented amorphous structure, the piezoelectric properties of the vinylidene fluoride-trifluoroethylene copolymer can be improved. One embodiment of the present application also provides a piezoelectric body, including the piezoelectric polymer film.

[0038] The piezoelectric polymer film of the present application has good flexibility and biocompatibility, as well as excellent piezoelectric properties. It is used in piezoelectric bodies, such as wearable devices, sensors, actuators, medical monitoring and energy harvesting devices, which is beneficial to improving the conversion efficiency between mechanical energy and electrical energy of the piezoelectric body.

[0039] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0040] Embodiment 1: In the first step, vinylidene fluoride-trifluoroethylene copolymer is added to N,N-dimethylformamide (DMF), the molar content of trifluoroethylene in the vinylidene fluoride-trifluoroethylene copolymer is 45%, and the weight average relative molecular mass of the vinylidene fluoride-trifluoroethylene copolymer is 450,000 g / mol. Stirring at room temperature for 12 hours obtains a uniform mixed solution, and the concentration of the vinylidene fluoride-trifluoroethylene copolymer in the mixed solution is 65 mg / mL.

[0041] In the second step, the obtained mixed solution was transferred to a glass culture dish and placed in a forced air oven at 55 °C for 24 h. After the film was formed, the film was peeled off from the glass culture dish to obtain a polymer film.

[0042] In the third step, the obtained polymer film was stretched at a stretching rate of 50 mm / min until the stretching ratio was 500%, and then annealed at 130 °C for 24 h.

[0043] In the fourth step, the stretched and annealed polymer film was unidirectionally polarized 40 times under an electric field of 150 MV / m.

[0044] Embodiment 2: The difference from Example 1 is that in the third step, the annealing temperature is adjusted to 70°C.

[0045] Embodiment 3: The difference from Example 1 is that in the third step, the annealing temperature is adjusted to 80°C.

[0046] Embodiment 4: The difference from Example 1 is that in the third step, the annealing temperature is adjusted to 90°C.

[0047] Embodiment 5: The difference from Example 1 is that in the third step, the annealing temperature is adjusted to 100°C.

[0048] Embodiment 6: The difference from Example 1 is that in the third step, the annealing temperature is adjusted to 110°C.

[0049] Embodiment 7: The difference from Example 1 is that in the third step, the annealing temperature is adjusted to 120°C.

[0050] Embodiment 8: The difference from Example 1 is that in the third step, the annealing temperature is adjusted to 140°C.

[0051] Embodiment 9: The difference from Example 1 is that in the third step, the annealing temperature is adjusted to 150°C.

[0052] Comparative Example 1: The difference from Example 1 is that in the first step, the vinylidene fluoride-trifluoroethylene binary copolymer is replaced by polyvinylidene fluoride (PVDF).

[0053] The present application conducted performance tests on the piezoelectric polymer films of Examples 1-9 and Comparative Example 1, including: (1) Determination of oriented amorphous structure content: The above polymer piezoelectric film was subjected to wide-angle X-ray scattering test, the two-dimensional result graph was converted into a one-dimensional result graph, and the Gauss+Lorentz Area function was used to perform peak fitting. The percentage of different contents was calculated.

[0054] (2) Determination of dielectric constant: The above-mentioned piezoelectric polymer film was subjected to a variable temperature dielectric constant test in the temperature range of -50°C to 200°C, and different dielectric constant values ​​at 10 Hz were statistically analyzed.

[0055] (3) Determination of remanent polarization value: The bidirectional hysteresis loop of the polymer piezoelectric film was measured, and the remanent polarization intensity under the electric field of 100 MV / m to 170 MV / m was observed and statistically analyzed.

[0056] (4) Direct piezoelectric coefficient test: The piezoelectric polymer film was assembled into a piezoelectric test sample, and its direct piezoelectric coefficient was tested on a quasi-static piezoelectric test device to obtain the direct piezoelectric coefficient (d 33 ), d 33 =Q / F, where Q is the change in charge and F is the applied force.

[0057] The above test results of the piezoelectric polymer films of Examples 1-9 and Comparative Example 1 of the present application are shown in Table 1. Among them, the test results trend of the direct piezoelectric coefficients of Examples 1-9 are shown in Table 1. Figure 1 , Figure 1 In the specific annealing temperature range, the piezoelectric polymer film has a good direct piezoelectric coefficient, and the higher the annealing temperature, the better. When the polarization reaches about 40 times, the piezoelectric polymer film of each embodiment has a good direct piezoelectric coefficient. d 33 The value can reach the maximum. Experiments have found that within a certain range, increasing the polarization times is beneficial to the piezoelectric properties of the piezoelectric polymer film, but the direct factors affecting the piezoelectric properties are still mainly the stretching ratio and annealing temperature.

[0058] Table 1. Performance test results of piezoelectric polymer films of Examples 1-9 and Comparative Example 1 of the present application In the present application, the preparation method of the piezoelectric polymer film is improved, and the polymer piezoelectric film is prepared by using a vinylidene fluoride-trifluoroethylene copolymer as a polymer raw material. Stress is applied to the polymer film to stretch it until the stretching ratio reaches a preset range, so that the polymer molecular chain structure has a favorable orientation. At the same time, the polymer film is annealed at a suitable temperature to increase the content of the oriented amorphous structure in the polymer film, improve the ferroelectric phase domain structure, and further strengthen the polarization to flip the dipoles so that as many as possible are arranged on the same side, so that the obtained piezoelectric polymer film has a higher dielectric constant, residual polarization strength and direct piezoelectric coefficient. d 33 .

[0059] On this basis, in Example 7, Example 1 and Example 8, the annealing temperature is further controlled within the range of 120°C to 140°C. Since the orientation of the amorphous structure of the polymer in the polymer film is sensitive to the annealing temperature under the specific stretching ratio set in the present application, further controlling the annealing temperature within this range can better promote the formation of the oriented amorphous structure in the polymer film, thereby improving the residual polarization strength and d 33 Example 9 uses a slightly higher annealing temperature. Based on the preset stretching, the oriented amorphous structure of the polymer is connected to the crystalline region. At this time, the excessively high temperature affects the crystalline region and also affects the mobility of the oriented amorphous structure of the polymer. Therefore, the residual polarization strength and d 33 It is lower than that of Examples 7, 1 and 8.

[0060] Compared with Example 1, the polymer raw material in Comparative Example 1 is replaced with polyvinylidene fluoride, and the β-crystalline content and polarity of the piezoelectric polymer film formed therefrom are not as good as those in the present application. Therefore, the dielectric constant, residual polarization strength and d 33 Relatively low.

[0061] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A method for preparing a piezoelectric polymer film, characterized in that: The preparation method comprises: providing a polymer film, the polymer film comprising a vinylidene fluoride-trifluoroethylene copolymer; stretching the polymer film so that the strain of the polymer film reaches 350% to 650%; and The stretched polymer film is annealed at a temperature of 70° C. to 150° C. to obtain the piezoelectric polymer film.

2. The preparation method according to claim 1, characterized in that The annealing temperature is 120° C. to 140° C., and the annealing time is 20 h to 26 h.

3. The preparation method according to claim 1, characterized in that The preparation method further comprises applying an electric field to the annealed polymer film for polarization, wherein the intensity of the electric field is 100 MV / m to 200 MV / m.

4. The preparation method according to claim 1, characterized in that: The vinylidene fluoride-trifluoroethylene copolymer satisfies at least one of the following conditions: (1) In the vinylidene fluoride-trifluoroethylene copolymer, the molar content of trifluoroethylene is 40% to 60%; (2) The weight average relative molecular mass of the vinylidene fluoride-trifluoroethylene copolymer is 400,000 g / mol to 550,000 g / mol.

5. The preparation method according to claim 1, characterized in that: The providing of the polymer film comprises mixing a vinylidene fluoride-trifluoroethylene copolymer with a solvent, wherein the solvent comprises one or more of N,N-dimethylformamide, acetone and dimethyl sulfoxide to obtain a mixed solution, and drying the mixed solution to obtain the polymer film.

6. The preparation method according to claim 5, characterized in that In the mixed solution, the concentration of the vinylidene fluoride-trifluoroethylene copolymer is 61 mg / mL to 83 mg / mL.

7. The preparation method according to claim 5, characterized in that The drying temperature is 35° C. to 65° C., and the drying time is 20 h to 26 h.

8. The preparation method according to claim 3, characterized in that: The polarization includes unidirectional polarization, and the number of the unidirectional polarization is 20 to 60 times.

9. A piezoelectric polymer film, characterized in that: The piezoelectric polymer film is prepared by the preparation method according to any one of claims 1 to 8.

10. A piezoelectric film device, characterized in that: The piezoelectric film device comprises the piezoelectric polymer film according to claim 9.